Noni (Morinda citrifolia) Modulates the Hypothalamic Expression of Stress- and Metabolic-Related Genes in Broilers Exposed to Acute Heat Stress - Rajaei-Sharifabadi, Hossein; Ellestad, Laura; Porter, Tom; Donoghue, Annie; Bottje, Walter G.; Dridi, Sami (Frontiers in Genetics, 2017)
Heat stress (HS) adversely affects growth performance and inflicts heavy economic losses to the poultry industry. There is, therefore, a critical need to identify new alternative strategies to alleviate the negative effects induced by HS. The tropic medicinal plant, Morinda Citrifolia (Noni), has been reported to improve feed intake and growth performance in poultry, however its underlying molecular mechanisms are still unknown. The present study aimed to determine the effect of Noni on feeding and drinking behavior as well as on the hypothalamic expression of stress- and metabolic-related genes in broiler chickens exposed to acute HS. A total of 480 one day-old male broiler chicks were randomly assigned to 12 controlled environmental chambers. Birds were subjected to two environmental conditions (TN, 25°C vs. HS, 35°C for 2h) and fed two diets (control vs. 0.2% Noni) in a 2x2 factorial design. Feed intake and core body temperature (BT) were recorded during HS period. Blood was collected and hypothalamic tissues were harvested for target gene and protein analyses. Acute HS-broilers exhibited higher BT (~1°C), spent less time eating with a significant decrease in feed intake, and spent more time drinking along with higher drinking frequency compared to those maintained under TN conditions. Although Noni supplementation did not improve feed intake, it significantly delayed (~30 min) and reduced the BT-induced by HS. At molecular levels and under HS conditions, Noni supplementation down regulated the hypothalamic expression of HSP90 and its related transcription factors HSF1, 2, and 4, increased orexin mRNA levels, and decreased the phosphorylation levels of AMPKα1/2 Thr172 and mTOR Ser2481. Together, these data indicated that Noni supplementation might modulate HS response in broilers through central orexin-AMPK-mTOR pathways.